Biochemical Behaviours of Salmeterol/Fluticasone Propionate in Treating Asthma and Chronic Obstructive Pulmonary Diseases (COPD) - Hilla Mills; Ronald Acquah; Nova Tang; Luke Cheung; Susanne Klenk; Ronald Glassen; Magali Pirson; Alain Albert; Duong Trinh Hoang; Thang Nguyen Van (Emergency Medicine International)
Chronic obstructive pulmonary diseases (COPD) and asthma are fatal. The respiratory tract may be blocked, robbed of the adequate amounts of oxygen; hence, death ensues if a quick medical attention is not provided. The treatment available for the duo are inhaled corticosteroids (ICS). The ICS can work synergically with LABAS (long-acting β2-antagonists) and so many other medicines like bronchodilators. The drugs used for the treatment of asthma and COPD are metabolised once in the body system and at the same time exerting the therapeutic effect provided the concentration of the drug is within the therapeutic window. The CYP3A isoforms metabolise the ICS, in this case, salmeterol and fluticasone propionate (FP). Methods of administration are not limited to inhalation. Specific doses are prescribed accurately paying attention to factors like age, gender, race, and genetic makeup since these affect drug metabolisms. Generally, the ICS work by translocating glucocorticoid receptors to the nucleus from the cytosol. The mechanism is potentiated by the β-antagonists and this brings about an anti-inflammatory effect which is greater than either of the two drugs alone. Once this happens, it is not necessary to increase ICS dose. The ICS, in addition, cause more production of β-receptors by activating the β-receptor genes. This mode of action begets the LABAs’ bronchodilator-effects. The challenge is that ICS are not limited only to “double” therapy. Analysing such therapies is daunting since coadministration interferes with pharmacology and pharmacokinetics of drugs. This work focuses on salmeterol/fluticasone propionate combination and aspects which has to do with administration, monitoring, metabolism, toxicity, and adverse effects.